2013
DOI: 10.1371/journal.ppat.1003577
|View full text |Cite
|
Sign up to set email alerts
|

TRIM5 alpha Drives SIVsmm Evolution in Rhesus Macaques

Abstract: The antagonistic interaction with host restriction proteins is a major driver of evolutionary change for viruses. We previously reported that polymorphisms of the TRIM5α B30.2/SPRY domain impacted the level of SIVsmm viremia in rhesus macaques. Viremia in macaques homozygous for the non-restrictive TRIM5α allele TRIM5Q was significantly higher than in macaques expressing two restrictive TRIM5alpha alleles TRIM5TFP/TFP or TRIM5Cyp/TFP. Using this model, we observed that despite an early impact on viremia, SIVsm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 79 publications
(109 reference statements)
2
55
0
Order By: Relevance
“…When Gag capsid sequences from SIVsm804E were compared with the parental SIVsmE543-3, we observed two amino acid substitutions in the cyclophilin A binding loop (L89I and A91P). These two substitutions are at the tip of the loop, which is known to be important for resistance to the host TRIM Cyp allele (30). Analysis of gag sequences of historical viral stocks revealed that these two amino acid substitutions were already present in SIVsmH631Br, and they were conserved in following passages (data not shown).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When Gag capsid sequences from SIVsm804E were compared with the parental SIVsmE543-3, we observed two amino acid substitutions in the cyclophilin A binding loop (L89I and A91P). These two substitutions are at the tip of the loop, which is known to be important for resistance to the host TRIM Cyp allele (30). Analysis of gag sequences of historical viral stocks revealed that these two amino acid substitutions were already present in SIVsmH631Br, and they were conserved in following passages (data not shown).…”
Section: Resultsmentioning
confidence: 96%
“…We have previously reported that certain host TRIM5␣ genotypes restrict replication of SIVsmE543-3 replication in vivo (29,30). Rhesus TRIM5 genotypes can be characterized based on polymorphisms at position 339 to 341 as permissive (TRIM Q/Q ), moderately susceptible (TRIM TFP/Q and TRIM Q/CypA ), or restrictive (TRIM TFP/TFP , TRIM TFP/CypA , and TRIM CypA/CypA ) for SIVsmE543-3.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the CA proteins of both SIVmac and SIVmne have the glutamine-glutamine pair at positions 89 and 90. Thus, after cross-species transmission of the group GP SIVsmm, TRIMCyp in the new hosts likely drove the evolution of the group Q SIVmac and SIVmne viruses (56). Restriction factors like TRIMCyp or TRIM5␣ may likewise have provided selection pressure for the evolution of group Q SIVs in other monkey species.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous control of viral replication has been observed in at least two macaque species (rhesus and cynomolgus) with specific MHC or TRIM5a alleles [35][36][37]. Some SIVagm strains (SIVagm.ver90 and SIVagm.…”
Section: Animal Models Of Spontaneous Protectionmentioning
confidence: 99%